The Dialectics of Hadith Authenticity: An Epistemological Dispute between Juynboll and Mustafa al-ʿAzami: Dialektika Otentisitas Hadis: Pergulatan Epistemologis antara Juynboll dan Mustafa al-ʿAzami - Ulin, Indina; Elua, Athaya Salsabila; Widya Cakti, Abiyyu Padma (Institut Agama Islam Negeri Kerinci, 2025)
This study analyzes the thoughts of G.H.A. Juynboll and Mustafa al-ʿAami regarding hadith authenticity, focusing on Juynboll’s Common Link theory and al-ʿAzami’s critique. Juynboll asserts that many hadiths in Islamic literature are products of isnad fabrication, centered on a key transmitter (common link), suggesting that such hadiths may not genuinely originate from the Prophet Muhammad. Conversely, al-’Azami argues that the isnad system has existed since the Prophet’s time and was meticulously preserved by hadith scholars. This research employs a qualitative-descriptive library study method. Primary data were obtained from the original works of both scholars and relevant secondary sources. The findings reveal that while the Common Link theory is helpful in mapping transmission chains, it is insufficient to question hadith authenticity without robust historical evidence. Al-’Azami’s critique highlights the importance of the narrators’ credibility and the continuity of the isnad as fundamental principles in hadith science. The study concludes that although Juynboll’s theory offers methodological value, its application must be approached cautiously to avoid contradicting the well-established principles of hadith authentication.